Effect of Wearing Medical Masks on Perioperative Respiratory Complications in Older Adults with Hip Fracture: A Retrospective Cohort Study - Fu M (Dove Medical Press, 2021)
Mingming Fu,1,* Junfei Guo,2,* Yaqian Zhang,1 Yuqi Zhao,1 Yingze Zhang,2– 4 Zhiqian Wang,1 Zhiyong Hou2,3 1Department of Geriatric Orthopedics, The Third Hospital of Hebei Medical University, Shijiazhuang, Hebei, People’s Republic of China; 2Department of Orthopaedic Surgery, the Third Hospital of Hebei Medical University, Shijiazhuang, Hebei, 050051, People’s Republic of China; 3NHC Key Laboratory of Intelligent Orthopaedic Equipment (The Third Hospital of Hebei Medical University), Shijiazhuang, China; 4Chinese Academy of Engineering, Beijing, 100088, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yingze ZhangThird Hospital of Hebei Medical University, Department of Orthopaedic Surgery, Shijiazhuang, Hebei, 050051, People’s Republic of ChinaEmail dryzzhang@126.comZhiqian WangThird Hospital of Hebei Medical University, Department of Geriatric Orthopedics, Shijiazhuang, Hebei, 050051, People’s Republic of ChinaEmail w18533112890@163.comPurpose: Respiratory complication is one of the major challenges in the treatment of older adults with hip fractures. However, no study so far has investigated the effect of wearing medical masks on the prevention of perioperative respiratory complications in these patients.Patients and Methods: In this retrospective cohort study, 1016 consecutive patients aged ≥ 65 years with hip fractures were included and assigned to two groups: the control group and the observation group. The two groups received the same perioperative management modalities. In addition, patients in the observation group were asked to wear medical masks for protection. Data of patients’ demographics, fracture type, surgical methods, comorbidities, the incidence of perioperative respiratory and other complications, and hospital outcomes were collected and compared between the two groups. Subgroup analyses were also performed stratified by fracture types.Results: A total of 1016 patients (292 females and 724 males) with a mean age of 79.4± 7.3 years were analyzed in the study, including 533 in the control group and 483 in the observation group. The overall incidence of perioperative respiratory complication, and the incidence of pulmonary infection, respiratory failure and arrhythmia in the observation group were significantly lower than the control group, especially in winter and spring. There was no difference in other complications, hospital length of stay, and total hospital costs. Further subgroup analyses showed that the incidence of heart failure and arrhythmia in the observation group was lower than that in the control group for patients with femoral neck fractures, which was different from patients with intertrochanteric fractures.Conclusion: The incidence of perioperative respiratory complications, including pulmonary infection and respiratory failure, could be reduced in older adults with hip fractures by strengthening personal protection, including wearing medical masks, especially in winter and spring. Wearing medical masks could also effectively reduce the incidence of perioperative heart failure and arrhythmia in femoral neck fracture patients and do not increase the incidence of other complications and the burden of hospitalization.Keywords: masks, aged, hip fractures, perioperative period, respiratory system